A Universal Approach to Crosslinked Hierarchical Polymer Multilayers as Stable and Highly Effective Antifouling Coatings. (20th March 2014) - Wei, Qiang; Becherer, Tobias; Noeske, Paul‐Ludwig Michael; Grunwald, Ingo; Haag, Rainer
<x xml:space="preserve">Abstract</x> Material‐independent and bioinert hierarchical polymer multilayer coatings are presented. Chemically active catecholic hyperbranched polyglycerols (hPGs) form a foundation layer on a versatile surface via multivalent anchoring and crosslinking, the activity of which is shielded by the bioinert catecholic hPGs. Mono‐catecholic hPGs finally terminate all of the free catechols to build a flexible bioinert top layer. These coatings perfectly prevent protein and cell adhesion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>